Le fonti della crisi: fra esigenze unitarie e garanzie costituzionali nel governo dell’emergenza da CoViD-19 (TEST BioLaw Journal - Rivista di BioDiritto, 2020)
This article analyses the effects the spreading of CoViD-19 had on the constitutional balance, both in Parliament-Government relations and State-Regions relations. It primarily deals with the legality of the decrees promoted by Italy’s Prime Minister (adopted under the provisions of a decree-law) and the utter importance of a uniform instrument for the central government to coordinate the measures adopted by the various Regions to fight the virus back. Then, we claim the necessity of a) an emergency constitutional proceeding to regulate the powers of Government and Parliament; and b) a “supremacy clause” to strengthen the central government.
Keywords: CoViD-19; pandemic emergency; multilevel governance; state of emergency; role of Parliament